Divergent trajectories in pancreatic cancer burden among older adults (55+): a GBD 2021 analysis revealing China’s dual epidemic of aging and population growth (1990–2045) - Dong, Hui; Wang, Heng; Han, Wenping; Niu, Haigang (Frontiers in Public Health, 2025)
BackgroundThe global population aging trend has intensified concerns regarding pancreatic cancer (PC), a leading cause of cancer-related mortality with a 5-year survival rate of 13%. This study evaluates the global burden, temporal trends, and socioeconomic disparities of PC among individuals aged ≥55 years using the 2021 Global Burden of Disease (GBD) data.MethodsAge-standardized incidence, prevalence, mortality, and disability-adjusted life years (DALYs) were analyzed across 204 countries. Joinpoint regression identified temporal trends (1990–2021), while Bayesian Age-Period-Cohort (BAPC) modeling projected future burden. Socioeconomic disparities were assessed via the Socio-demographic Index (SDI), and risk factor contributions were quantified using decomposition analysis.ResultsIn 2021, Finland, Germany, and Japan exhibited the highest age-standardized PC prevalence (ASPR: 64.42–66.17 per 100,000 population), contrasting sharply with Mozambique (ASPR: 2.85 per 100,000 population). Mortality peaked in Greenland (age-standardized death rate, ASDR: 81.85 per 100,000 population) and Monaco (ASDR: 71.75 per 100,000 population). Males showed elevated burden across incidence, prevalence, and mortality (peak age: 70–74 years), with global trends persistently rising (average annual percentage change, AAPC >0, 1990–2021). China experienced a transient mortality decline (AAPC = −0.93, 2011–2015), linked to healthcare reforms. High SDI regions (e.g., Japan) faced amplified burdens driven by aging and metabolic risks, while smoking (15.4–28.5% of deaths and years lived with disability, YLDs) and hyperglycemia (37.8% of YLDs in the U.S.) dominated modifiable risks. Projections diverge significantly: China’s age-standardized incidence rate (ASIR) burden is projected to increase from 27.96 (95% uncertainty interval, UI: 25.76, 30.16) in 2022 to 36.94 (UI: 0, 79.46) by 2045. In contrast, the global ASIR is expected to decline from 31.07 (UI: 30.06, 32.08) to 27.11 (UI: 8.73, 45.57).ConclusionPersistent socioeconomic and gender disparities underscore the need for targeted interventions, including tobacco control, glycemic management, and lifestyle modifications. Prioritizing aging populations in high-SDI regions and addressing underreported risks in low-SDI areas are critical for mitigating the growing PC burden.